KAUSALITAS INSPEKSI KESELAMATANDAN KESEHATAN KERJA DENGAN TINGKAT KECELAKAAN KERJA - Marwansyah, Sofyan (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2012)
Technological developments have raised the standard of living humans. However, technological advances also bring the sources of job stress and a new injury. A completev modern technology, changes informs of employment, work organization, and production systems place high demands on a working power.As a result, the level rmdform of the potential hazards in the workpla9e that should be in the face of workers will also change. To overcome this required the implementation of performance improvement in a company K3. This thesis research conducted at the cement plant at PT Indocement Tunggal Prakarsa Tbk that in every work area contains potential hazards that threaten the welfare of workers. In building peiformance implementation of K3, PT Indocement. Has sought to reduce or eliminate the potential hazard in the factory area with implementing this program is one of the K3 inspections (safety monitoring}. Implementation of inspection programs K3 also influence the level of workplace accidents, because in principle every incident can be prevented. Therefore, it is determined by the quantity and quality of inspections so that potential hazards can be known earlier that the results could reduce workplace accidents that might happen.